Brain substrate metabolism and ß‐cell function in humans: A positron emission tomography study. Issue 3 (19th April 2020) - Rebelos, Eleni; Mari, Andrea; Bucci, Marco; Honka, Miikka‐Juhani; Hannukainen, Jarna C.; Virtanen, Kirsi A.; Hirvonen, Jussi; Nummenmaa, Lauri; Heni, Martin; Iozzo, Patricia; Ferrannini, Ele; Nuutila, Pirjo
Abstract: Aims: Recent clinical studies have shown enhanced brain glucose uptake during clamp and brain fatty acid uptake in insulin‐resistant individuals. Preclinical studies suggest that the brain may be involved in the control of insulin secretion. The aim of this study was to investigate whether brain metabolism assessed as brain glucose and fatty acid uptake is associated with the parameters of β‐cell function in humans. Materials and methods: We analysed cross‐sectional data of 120 subjects across a wide range of BMI and insulin sensitivity. Brain glucose uptake (BGU) was measured during euglycaemic‐hyperinsulinaemic clamp (n = 67) and/or during fasting (n = 45) using [ 18 F]‐fluorodeoxyglucose (FDG) positron emission tomography (PET). In another group of subjects (n = 34), brain fatty acid uptake was measured using [ 18 F]‐fluoro‐6‐thia‐heptadecanoic acid (FTHA) PET during fasting. The parameters of β‐ cell function were derived from OGTT modelling. Statistical analysis was performed with whole‐brain voxel‐based statistical parametric mapping. Results: In non‐diabetics, BGU during euglycaemic hyperinsulinaemic clamp correlated positively with basal insulin secretion rate ( r = 0.51, P = .0008) and total insulin output ( r = 0.51, P = .0008), whereas no correlation was found in type 2 diabetics. BGU during clamp correlated positively with potentiation in non‐diabetics ( r = 0.33, P = .02) and negatively in type 2 diabetics ( r = −0.61, P = .02). The associations in non‐diabetics were not explained with whole‐body insulin sensitivity or BMI. No correlations were found between baseline (fasting) BGU and basal insulin secretion rate, whereas baseline brain fatty acid uptake correlated directly with basal insulin secretion rate ( r = 0.39, P = .02) and inversely with potentiation ( r = −0.36, P = .04). Conclusions: Our study provides coherent, though correlative, evidence that, in humans, the brain may be involved in the control of insulin secretion independently of insulin sensitivity. Abstract : Preclinical studies suggest that the brain may be involved in the control of insulin secretion, but data on humans are scanty. Our study provides coherent, though correlative, evidence that, in humans, the brain may be involved in the control of insulin secretion independently of insulin sensitivity.